Demonstrating the impact of ro-vibrationally excited H2 on divertor detachment via population modelling - Richard C. Bergmayr; Dirk Wünderlich; Mathias Groth; Liam H. Scarlett; Dmitry V. Fursa; Mark C. Zammit; Igor Bray; Ursel Fantz (Nuclear Materials and Energy)
EDGE2D-EIRENE profiles characteristic for low recycling, high recycling and detached plasmas are postprocessed applying a vibrationally resolved collisional radiative (CR) model based on the Yacora solver to predict excited state densities and thus the molecular Lyman-, Werner- and Fulcher band emission intensities. These emission intensities are compared to predictions from the AMJUEL database standardly used in EIRENE. Lower Fulcher band and higher Lyman- and Werner band emission is predicted by the Yacora model in comparison to AMJUEL suggesting that inconsistent results from model based evaluation of measured spectra are expected depending on which model and molecular emission band is considered. The implications on detachment rate predictions are discussed.